Dental Pulp Stem Cells Derived From Adult Human Third Molar Tooth: A Brief Review - Al Madhoun, Ashraf; Sindhu, Sardar; Haddad, Dania; Atari, Maher; Ahmad, Rasheed; Al-Mulla, Fahd (Frontiers in Cell and Developmental Biology, 2021)
The fields of regenerative medicine and stem cell-based tissue engineering have the potential of treating numerous tissue and organ defects. The use of adult stem cells is of particular interest when it comes to dynamic applications in translational medicine. Recently, dental pulp stem cells (DPSCs) have been traced in third molars of adult humans. individuals. DPSCs have been isolated and characterized by several groups. DPSCs have promising common characteristics including self-renewal capacity, rapid proliferation, colony formation, multi-lineage differentiation and pluripotent gene expression profile. Nevertheless, genotypic, and phenotypic heterogeneities have been reported for DPSCs subpopulations, which may influence their therapeutic potentials. The underlying causes of DPSCs’ heterogeneity remain poorly understood; however, the heterogeneity emerges as a consequence of an interplay between intrinsic- and extrinsic- cellular factors. The main objective of the paper is to Herein, we review the current literature and perspectives on related to the human DPSCs derived from the third molar, residential DPSCs with a focus focusing on their physiological properties, isolation procedures, and culture conditions, , as well as, the internal and external regulatory signaling mechanism that regulate their self-renewal, proliferation, and lineage differentiation capacities and their prospective advances use in pre-clinical and clinical applications..